Educational Technology in Elementary Teaching: Philosophies and Practices of Selected Teachers - Reyes, Monica Sophia; San Buenaventura-Gaza, Joy (Journal of Pedagogy and Education Science, 2025)
Technology is present in almost all of society, including education. While there is increased use of various forms of technology and their applications, it is also essential to understand the philosophies and beliefs of elementary teachers and their decision points in incorporating technology into their teaching practice. This study aimed to systematically review the educational technology used in elementary teaching and document and describe the philosophies and practices of selected teachers. The researcher used the PRISMA model to review literature and group best practices into five areas: Teaching Methods, Instructional Materials, Interaction and Collaboration, Assessment, and Accessibility. Data was collected through surveys and a Focus Group Discussion (FGD). One survey question used SAMR descriptors to assess how often and in what ways teachers used technology in class. These helped identify which practices worked well for both teachers and students. To see if teachers followed best practices found in literature, the researcher included them in the survey and confirmed them in the FGD. A Teaching Philosophy test also identified each teacher's dominant philosophy. Results were analyzed qualitatively. The study found that even with some challenges, elementary teachers used technology in varied ways aligned with global best practices. The literature review highlighted effective strategies from countries like the US, the UK, Singapore, Japan, and Canada, offering models the Philippines can adopt or adapt. It also showed that teaching philosophy did not affect how teachers applied technology in their classrooms.